(3OjhGf GdeYGfis - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO GHf jMji Hf egQGf GdnYrSncQj, CHh gdGd,J (B395 (3g` s ((3eMSf Hf CHj GdaVd GdebQi GdhGSWi s)
(3ChdgG (B:s
(3LeYJ ai gPG GdcJGH CHdZ eGLGA ai cd af CHQY eGQhi ai cd fhY ef CYdGe GdeYGfi hCYGfgG Edi YhGO HgG hTPGJgG, hJNjQJ ef Pdc eGcGf LjOG dfXe eMce GdQUa ZjQ egdgd hdG QNh hdG eJLYO aL CdN s
(3JTJed Ydi GdHGH GdQGHY Edi GdKGfi YTQs
(3QJHg Ydi EKfi YTQ HGkHs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B240s
Keywords: (3GdCOHs